(untitled) (Western European Journal of Linguistics and Education, 2024)
In this article, the specific features of gender linguistics were analyzed from the point of view of linguistics, and its manifestation in speech and pragmatic classification were selected as the main object of the article. It should be noted that the analysis of gender linguistics as a source of analysis causes it to be evaluated as the main object in speech relations today. In addition, the article demonstrates the ideas of gender linguistics with the help of examples